Grand strategy in US and China foreign policy: seeking world hegemony or promoting global harmony? - Kaviaka, Iryna I. (Journal of the Belarusian State University. International Relations, 2024)
The dawn of the 21st century has witnessed seismic shifts in the dynamics of international relations and the global strategies of leading powers. The US and China, as major players in the world arena, confront both shared threats and unique national characteristics for the first time in history. Discussion of a great power’s foreign policy typically involves an exploration of its grand strategy. However, interpretations of this concept can vary significantly, influenced by each nation’s political philosophy, historical trajectory, and geopolitical priorities. This article aims to elucidate the stable theoretical underpinnings of the US and Chinese global policies, to compare their ultimate aspirations within their grand strategies and the way they seek to achieve these goals, to examine their mutual perceptions in global politics, often marked by misunderstandings, to assess whether the American model of world hegemony and the Chinese vision of global harmony are compatible within contemporary international relations.